Keberlanjutan Usaha Peternakan Sapi Potong Program Bantuan Pemerintah Di Kabupaten Padang Pariaman - Tommy Fadillah; Ira Wahyuni Syarfi; Asdi Agustar (Jurnal Niara, 2023)
This study aims to determine the sustainability of the government-assisted beef cattle business in Padang Pariaman Regency and the factors that influence it. The study was conducted using a survey method with respondents of 82 beneficiaries in 2013 to 2017. Data collection using questionnaires. Data analysis using descriptive statistics and multiple linear regression correlation analysis. The results of the study found that the sustainability of the government-assisted beef cattle business in Padang Pariaman Regency was seen physically and economically as showing a low level of sustainability. This is due to the weakness in planning, implementing and supervising the assistance provided to the community by paying attention to variables that are very sensitive to the sustainability of the beef cattle farming business so that the expected goals have not been achieved properly